Shared Decision-Making Based Structured Communication in Improving Patient Understanding and Patient Safety - Diaz Alifarizki Zuvarcan; Dasrun Hidayat; Mira Veranita (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
Clinical communication failures and low patient involvement are the primary causes of patient safety incidents in hospitals. The asymmetrical communication in the inpatient wards of RSUD Dr. Moewardi potentially reduces patient understanding, particularly in chronic cases involving high-risk therapies. This study aims to explore the implementation of a structured communication system based on Shared Decision-Making (SDM) and to measure its impact on enhancing patient understanding (health literacy) and strengthening personalized-care-based patient safety. This study employs a Mixed Methods Sequential Exploratory design. The qualitative exploratory phase involves in-depth interviews with 11 informants (healthcare professionals, head nurses, and patients/families) to investigate the implementation of communication and its barriers in the field. These findings serve as the foundation for developing quantitative instruments, which will be distributed to 96 healthcare professionals using a proportionate stratified random sampling technique. The data will be analyzed using inferential statistics to evaluate the effects and mediation among variables. The results are expected to demonstrate that health literacy significantly mediates the impact of structured communication on patient safety. The implications of this study are projected to provide a strategic foundation for hospital management to reconstruct bedside handover and educational guidelines, making them more personal and participatory to prevent Adverse Events (AEs).